Rapid, B1-insensitive, dual-band quasi-adiabatic saturation transfer with optimal control for complete quantification of myocardial ATP flux - Miller, JJ; Valkovič, L; Kerr, M; Timm, KN; Watson, WD; Lau, JYC; Tyler, A; Rodgers, C; Bottomley, PA; Heather, LC; Tyler, DJ (Wiley, 2021)
Purpose: Phosphorus saturation-transfer experiments can quantify metabolic fluxes non-invasively. Typically, the forward flux through the creatine-kinase reaction is investigated by observing the decrease in phosphocreatine (PCr) after saturation of γ-ATP. The quantification of total ATP utilisation is currently under-explored, as it requires simultaneous saturation of inorganic phosphate (Pi) and PCr. This is challenging, as currently available saturation pulses reduce the already-low γ-ATP signal present.